Does residual bone thickness apical to periodontal defect play a major role in maxillary sinus mucous membrane thickness?: A cone-beam computed tomography-assisted retrospective study - Vijay Apparaju; Sai Charitha Velamati; Lasya Karnati; Amir Salahshoor; Fatemeh Nateghi; Sunil Kumar Vaddamanu (Wolters Kluwer Medknow Publications, 2019)
Background: The mucous membrane of the maxillary sinus is very sensitive to foreign bodies and infections. Any triggering may lead to mucous membrane thickening (MMT). Residual bone thickness (RBT) is the remaining bone apical to the periodontal defect until the floor of the maxillary sinus acts as a barrier for the periodontal infections to reach the sinus. The aim of our current study was to evaluate the minimal RBT to prevent periodontal infection to reach Schneiderian membrane using cone-beam computed tomography (CBCT). Materials and Methods: In this descriptive study, 144 maxillary sinus exposure records of 100 patients were collected retrospectively. Patients with minimum one sinus exposure were considered. MMT and RBT were calculated with the CBCT assistance. Statistical analysis was done using Mann-Whitney U-test , Kruskal-Wallis and Chi-square test. (P < 0.05) was considered as statistically significant. Results: Significant difference (P < 0.001) was observed in MMT among three RBT groups. Significantly, higher mean MMT was observed with <2 mm and 2-4 mm RBT groups. The prevalence of MMT with >4 mm group is less (7%) compared to <2 mm group and 2-4 mm RBT groups (91.2% and 90.2%, respectively). Furthermore, there is no significant difference in MMT between angular and furcation defects (P = 0.890). Conclusion: Probability of MMT was increased if RBT is <4 mm. Early detection and prompt periodontal treatments associated with regenerative procedures can be instituted wherever possible to improve RBT and to reduce MMT. Further, microbiological studies are required to confirm the analysis.